Kinetics of Water Gas Shift Reaction on Au/CeZrO4: A Comparison Between Conventional Heating and Dielectric Barrier Discharge (DBD) Plasma Activation - Kanlayawat Wangkawong (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Abstract: The kinetics of the low-temperature forward water gas shift (LT-WGS) reaction have been studied over a 2 wt% Au/CeZrO4 (Au/CZO) catalyst using both thermal and dielectric barrier discharge plasma heterogeneous catalyst systems. Using the energy density (ε), the apparent activation energy has been calculated under plasma and thermally activated conditions. A substantially lower apparent activation energy is observed in the plasma activated system (9.5 kJ/mol) compared with the thermal-catalysed reaction (132.9 kJ/mol). Different kinetic isotope effect (KIE) values for water were found in thermal (1.43) and plasma (1.89) activated catalytic systems which infer different mechanisms between the two activation processes and also shows the importance of water activation. Furthermore, negative and positive reaction orders with respect to CO and H2O are found for both conditions which are − 1.30, 0.28 under thermal and − 1.53, 0.35 under plasma processes, respectively. The reaction order with respect to H2O and KIE studies demonstrate that the bond cleavage in H2O molecule is a rate determining step in the plasma-assisted LT-WGS, similar to that in the thermal-assisted reaction. Graphic Abstract: [Figure not available: see fulltext.].